Assessment of listing and categorisation of animal diseases within the framework of the Animal Health Law (Regulation (EU) No 2016/429): bluetongue - More, Simon; Bicout, Dominique; Bøtner, Anette; Butterworth, Andrew; Depner, Klaus; Edwards, Sandra; Garin-Bastuji, Bruno; Good, Margaret; Gortázar Schmidt, Christian; Michel, Virginie; Angel Miranda, Miguel; Nielsen, Søren Saxmose; et al. (Wiley, 2017)
A specific concept of strain was developed in order to classify the BTV serotypes ever reported in Europe based on their properties of animal health impact: the genotype, morbidity, mortality, speed of spread, period and geographical area of occurrence were considered as classification parameters. According to this methodology the strain groups identified were (i) the BTV strains belonging to serotypes BTV-1–24, (ii) some strains of serotypes BTV-16 and (iii) small ruminant-adapted strains belonging to serotypes BTV-25, -27, -30. Those strain groups were assessed according to the criteria of the Animal Health Law (AHL), in particular criteria of Article 7, Article 5 on the eligibility of bluetongue to be listed, Article 9 for the categorisation according to disease prevention and control rules as in Annex IV and Article 8 on the list of animal species related to bluetongue. The assessment has been performed following a methodology composed of information collection, expert judgement at individual and collective level. The output is composed of the categorical answer, and for the questions where no consensus was reached, the different supporting views are reported. The strain group BTV (1–24) can be considered eligible to be listed for Union intervention as laid down in Article 5(3) of the AHL, while the strain group BTV-25–30 and BTV-16 cannot. The strain group BTV-1–24 meets the criteria as in Sections 2 and 5 of Annex IV of the AHL, for the application of the disease prevention and control rules referred to in points (b) and (e) of Article 9(1) of the AHL. The animal species that can be considered to be listed for BTV-1–24 according to Article 8(3) are several species of Bovidae, Cervidae and Camelidae as susceptible species; domestic cattle, sheep and red deer as reservoir hosts, midges insect of genus Culicoides spp. as vector species.